2004
DOI: 10.1007/s00134-003-2124-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopexamine in comparison with fenoterol on carbohydrate, fat and protein metabolism in healthy volunteers

Abstract: Dopexamine has no or only weak effects on carbohydrate metabolism, its effects on fat and protein metabolism are comparable to those of fenoterol. This metabolic profile may be advantageous in increasing cardiac output in patients with impaired glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…IDAs are used to measure metabolites (17 ), small drug molecules in biological fluids (23,24 ), and large complex molecules such as peptide hormones (6,7,(13)(14)(15)(16)18 ). For reported C-peptide assays, the lowest amount measured was 30 fmoles on column, which was obtained via initial immunoprecipitation/SPE followed by off-line RP chromatography and direct MS detection (7 ); the detection limit was also 30 fmoles for ultrafiltration followed by RP LC/tandem MS (6 ).…”
Section: Discussionmentioning
confidence: 99%
“…IDAs are used to measure metabolites (17 ), small drug molecules in biological fluids (23,24 ), and large complex molecules such as peptide hormones (6,7,(13)(14)(15)(16)18 ). For reported C-peptide assays, the lowest amount measured was 30 fmoles on column, which was obtained via initial immunoprecipitation/SPE followed by off-line RP chromatography and direct MS detection (7 ); the detection limit was also 30 fmoles for ultrafiltration followed by RP LC/tandem MS (6 ).…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic disorders are often mediated by the endogenous sympathoadrenergic system and may be enhanced by the use of exogenous sympathomimetic drugs and particularly b 2adrenoceptor agonists. Geisser et al [39] examined 27 healthy male volunteers and compared the metabolic effects of dopexamine, a peripheral vasodilator with b 2agonist properties, to those of fenoterol, a pure b 2 -agonist. They demonstrated that, in contrast with fenoterol, dopexamine has no effect on carbohydrate metabolism (lack of variation in glucose plasma concentration and glucose clearance) and does not enhance gluconeogenesis.…”
Section: Metabolic Effectsmentioning
confidence: 99%